The Mulcahy Salvage: Past and Present Innovations. (November 2015) - Mellon, Matthew J.; Broghammer, Joshua R.; Henry, Gerard D.
Abstract: Introduction: Inflatable penile implants are a mainstay for the surgical correction of erectile dysfunction. For the last 40 years they have provided reliable outcomes with durable patient satisfaction. Infection of the implant continues to remain the primary surgical concern, despite the advent of antibiotic‐coated devices and improved skin preparation solutions. Methods: In this article, we review and evaluate the published literature for important contributions surrounding the various salvage techniques and washout strategies. In addition, the role of biofilm in prosthetic infection will be discussed. Results: First described by Mulcahy for instances of device infection, the salvage or rescue procedure was established to avoid complete removal and staged replacement. This approach, with its avoidance of difficult revision surgery, penile shortening and patient discomfort, has produced success as high as 84%. Conclusion: Mulcahy's innovative approach at salvage or rescue reimplantation has proven to be a highly successful approach to this difficult surgical problem. Without question, the report of the long‐term results of his salvage patients has directly influenced a generation of prosthetic surgeons.Mellon MJ, Broghammer JR, and Henry GD. The Mulcahy salvage: Past and present innovations. J Sex Med 2015;12(suppl 7):432–436.